Pengaruh Kepuasan Kerja, Pendidikan dan Pengalaman Kerja Terhadap Kinerja Manajer Perusahaan Manufaktur di Indonesia - Abriyani Puspaningsih (Jurnal Aplikasi Bisnis, 2017)
This research is aimed to expose the effect of some variables (job satisfaction, education and job experience) on the performance of manufacturing company managers in Indonesia. Respondents in this research were the managers of the big scale manufacturing companies in Indonesia. The data in this research were collected by quesionares which were sent by mail. Data processing in this study was supported by Statistics Program. The data analysis was carried on by regression analysis.The results from the analysis showed that job satisfaction affected the job performance of manufacturing company managers in Indonesia. Education and job experience not affected the performance of manufacturing company managers in Indonesia.